Resumos de Dissertações e Teses Defendidas - 1º Semestre 2019 - PPGH/Unioeste - Editorial, Equipe (Tempos Históricos, 2020)
Resumos de Dissertações e Teses Defendidas - 1º Semestre 2019 - PPGH/Unioeste